The effect of a supervised exercise training programme on sleep quality in recently discharged heart failure patients. (June 2015) - Suna, Jessica M; Mudge, Alison; Stewart, Ian; Marquart, Louise; O'Rourke, Peter; Scott, Adam
Background: Sleep disturbances, including insomnia and sleep-disordered breathing, are a common complaint in people with heart failure and impair well-being. Exercise training (ET) improves quality of life in stable heart failure patients. ET also improves sleep quality in healthy older patients, but there are no previous intervention studies in heart failure patients. Aim: The aim of this study was to examine the impact of ET on sleep quality in patients recently discharged from hospital with heart failure. Methods: This was a sub-study of a multisite randomised controlled trial. Participants with a heart failure hospitalisation were randomised within six weeks of discharge to a 12-week disease management programme including exercise advice ( n =52) or to the same programme with twice weekly structured ET ( n =54). ET consisted of two one-hour supervised aerobic and resistance training sessions, prescribed and advanced by an exercise specialist. The primary outcome was change in Pittsburgh Sleep Quality Index (PSQI) between randomisation and week 12. Results: At randomisation, 45% of participants reported poor sleep (PSQI≥5). PSQI global score improved significantly more in the ET group than the control group (–1.5±3.7 vs 0.4±3.8, p =0.03). Improved sleep quality correlated with improved exercise capacity and reduced depressive symptoms, but not with changes in body mass index or resting heart rate. Conclusion: Twelve weeks of twice-weekly supervised ET improved sleep quality in patients recently discharged from hospital with heart failure.